Salt-tolerant rootstock increases yield of pepper under salinity through maintenance of photosynthetic performance and sinks strength - Penella, Consuelo; Landi, Marco; Guidi, Lucia; Nebauer, Sergio G.; Pellegrini, Elisa; San Bautista, Alberto; Remorini, Damiano; Nali, Cristina; López-Galarza, Salvador; Calatayud, Ángeles (2017)
The performance of a salt-tolerant pepper (Capsicum annuum L.) accession (A25) utilized as a rootstock was assessed in two experiments. In a first field experiment under natural salinity conditions, we observed a larger amount of marketable fruit (+75%) and lower Blossom-end Root incidence (-31%) in commercial pepper cultivar Adige (A) grafted onto A25 (A/A25) when compared with ungrafted plants. In order to understand this behavior a second greenhouse experiment was conducted to determine growth, mineral partitioning, gas exchange and chlorophyll a fluorescence parameters, antioxidant systems and proline content in A and A/A25 plants under salinity conditions (80 mM NaCl for 14 days). Salt stress induced significantly stunted growth of A plants (-40.6% of leaf dry weight) compared to the control conditions, while no alterations were observed in A/A25 at the end of the experiment. Accumulation of Na+ and Cl- in leaves and roots was similar in either grafted or ungrafted plants. Despite the activation of protective mechanisms (increment of superoxide dismutase, catalase, ascorbate peroxidase activity and non-photochemical quenching), A plants showed severely reduced photosynthetic CO2 assimilation (-45.6% of A(N390)) and substantial buildup of malondialdehyde (MDA) by-product, suggesting the inability to counteract salt-triggered damage. In contrast, A/A25 plants, which had a constitutive enhanced root apparatus, were able to maintain the shoot and root growth under salinity conditions by supporting the maintained photosynthetic performance. No increases in catalase and ascorbate peroxidase activities were observed in response to salinity, and MDA levels increased only slightly; indicating that alleviation of oxidative stress did not occur in A/A25 plants. In these plants the increased proline levels could protect enzymatic stability from salt-triggered damage, preserving the photosynthetic performance. The results could indicate that salt stress was vanished by the lack of negative effects on photosynthesis that support the maintained plant growth and increased marketable yield of the grafted plants. (c) 2016 Elsevier GmbH. All rights reserved.